Perbedaan Kemampuan Menulis Naskah Drama dengan Model Pembelajaran Kontekstual Tipe Pemodelan dan Model Pembelajaran Kooperatif Tipe CIRC pada Siswa Kelas IX SMPN 2 Malalak - Mariratul Mawaddah; Atmazaki .; Ngusman Abdul Manaf (Bahasa, Sastra, dan Pembelajaran, 2013)
Abstract: This research aims to explain the differences in the ability to write a play using a model of the type of modeling contextual learning and cooperative learning model CIRC in class IX.1 SMP N 2 Malalak. Method used is pre experimental design. The selected research design was 2 x 2 factorial design with using a quantitative approach. Based on research data, obtained the following results. First, the ability to write a play class IX Junior High School students are learning Malalak CIRC model is not significantly different from that learned by modeling. Second, students with high prior knowledge taught by modeling obtain better value than the CIRC. Third, students with low prior knowledge taught by CIRC obtain better value than that taught by modeling. Fourth, there was an interaction between the model of learning with students' prior knowledge and skills plays menuis students in class IX SMP N 2 Malalak. The conclusion of this resaerch is that prior knowledge is a matter that needs to be considered in determining learning model that will be used. CIRC learning model used is well-suited for students who have lower prior knowledge.   Kata kunci: Kemampuan Menulis, Naskah drama, Model Pembelajaran Kontekstual, pemodelan, Model Pembelajaran Kooperatif, CIRC.